Leukocyte telomere attrition in cognitive decline: associations with APOE genotype and cardiovascular risk factors - Barros, Alexandre Guimarães de Almeida; Soares, Thayana Oliveira; Lage, Ariane Flávia Almeida; Cintra, Marco Túlio Gualberto; de Paula, Jonas Jardim; Malheiro, Olívio Brito; Falcão, Antonio Eiras; Nogueira, Christiano Altamiro Coli; de Carvalho, Leandro Braz; Romano Silva, Marco Aurélio; de Miranda, Debora Marques; Viana, Bernardo de Mattos; et al. (Frontiers in Aging Neuroscience, 2025)
Telomere shortening represents a fundamental mechanism of cellular aging potentially implicated in neurodegenerative processes. This study investigated the complex associations among leukocyte telomere length, cardiovascular risk profiles, and APOE polymorphisms in age-related cognitive decline. Through a cross-sectional analysis of 90 participants stratified by cognitive status into three groups: cognitively unimpaired (CU), mild cognitive impairment (MCI), and Alzheimer’s Disease (AD), we quantified relative telomere length using quantitative PCR, performed APOE genotyping and assessed cardiovascular risk factors. Quantitative analysis revealed significantly reduced telomere length in the AD group compared to CU and MCI groups. Multivariate regression analysis identified cognitive status as an independent predictor of telomere length (β = −0.468, p < 0.001). APOE ε4 carrier status showed higher prevalence in AD subjects as expected. Cardiovascular risk factors demonstrated no significant correlation with telomere length across cognitive groups. Our findings establish a robust association between telomere shortening and advanced cognitive impairment in AD, suggesting potential utility as a neurodegenerative biomarker. This relationship appears independent of traditional cardiovascular risk factors, highlighting the complexity of cellular aging mechanisms in neurodegeneration.